Human neutrophil lipocalin in fMLP-activated whole blood as a diagnostic means to distinguish between acute bacterial and viral infections - Venge, Per; Håkansson, Lena Douhan; Garwicz, Daniel; Peterson, Christer; Xu, Shengyuan; Pauksen, Karlis (Journal of immunological methods, 2015)
The distinction between causes of acute infections is a major clinical challenge. Current biomarkers, however, are not sufficiently accurate. Human neutrophil lipocalin (HNL) in serum distinguishes acute infections with high accuracy, but in the emergency setting the assay time should be <15–20min, which excludes the use of serum samples. The aim was therefore to develop a novel rapid assay principle and test its clinical performance. Serum and neutrophils obtained from 84 infected and 20 healthy subjects were used in the experimental study. 725 subjects (144 healthy controls and 581 patients with signs and symptoms of acute infections) were included in the clinical study. HNL was measured in EDTA-plasma by ELISA or in heparinized whole blood after fMLP activation by a prototype point-of-care assay. Increased release of HNL from neutrophils after activation with fMLP was seen already after 5min incubation. The release of HNL from purified neutrophils after 15min incubation with fMLP was significantly correlated to the HNL concentrations in serum obtained from the same patient (r=0.74, p<0.001). In the distinction between healthy controls and patients with bacterial infections, the areas under the ROC-curves were 0.95 (95% CI 0.91–0.97) and 0.88 (95% CI 0.84–0.91) for HNL in fMLP-activated whole blood and EDTA-plasma, respectively, (p<0.001) and in the distinction between bacterial and viral infections 0.91 (95% CI 0.86–0.95) and 0.76 (95% CI 0.70–0.81), respectively (p<0.001). The clinical performance of HNL in fMLP-activated whole blood was superior to HNL in EDTA-plasma and similar to HNL in serum. The procedure can be adopted for point-of-care testing with response times of <15min.